Ben B. Lindsey papers - Lindsey, Ben B. (Ben Barr), 1869-1943.
Correspondence; manuscripts of articles, books, speeches, plays, and broadcast scripts; notebooks; daybooks; journals; yearbooks; appointment books; stenographic notes; case files; financial and legal records; legislative files; official and personal files; Lindsey (Lindsay) family papers; memorabilia; newspaper clippings; scrapbooks; broadsides; photographs; and other papers primarily concerning Lindsey's role in the development of the juvenile court systems in Colorado and California, his tenure as judge in both states, and his political and literary activities. Subjects include child welfare, child labor laws, penal reform, women's suffrage, birth control, marriage and divorce, sex education and hygiene, and the Women's Protective League. Documents Lindsey's disbarment in Colorado, the Colorado mine strike incident, and the investigations of the Whittier State School of California in 1940-1942.
Correspondents include Jane Addams, Joseph P. Annin, Newton Diehl Baker, Roger N. Baldwin, Albert Jeremiah Beveridge, Edward William Bok, Louis Dembitz Brandeis, Henry Augustus Buchtel, Luther Burbank, Carrie Chapman Catt, James H. Causey, John Cavanaugh, Edward Prentiss Costigan, George Creel, Clarence Darrow, Stephen T. Early, Thomas A. Edison, Havelock Ellis, Robert Erskine Ely, Wainwright Evans, Harriet Ford, Henry Ford, Louis M. Howe, Charles Evans Hughes, Harold L. Ickes, Hiram Johnson, Tom Loftin Johnson, John Harvey Kellogg, Robert M. La Follette, Jesse L. Lasky, Walter Lippmann, Julian W. Mack, W.G. McAdoo, S.S. McClure, Jesse F. McDonald, H.H. McIntyre, Justin Miller, Henry Morgenthau, Harvey Jerrold O'Higgins, Culbert Levy Olson, Thomas McDonald Patterson, Drew Pearson, George W. Perkins, James H. Pershing, Amos Pinchot, Gifford Pinchot, Donald R. Richberg, Jacob A. Riis, Eleanor Roosevelt, Franklin D. Roosevelt, Theodore Roosevelt, Sol A. Rosenblatt, Bertrand Russell, Margaret Sanger, Hannah Kent Schoff, John F. Shafroth, Morrison Shafroth, Upton Sinclair, Lincoln Steffens, Lyman Beecher Stowe, William H. Taft, R.D. Thompson, Earl Warren, James E. West, William Allen White, Brand Whitlock, Woodrow Wilson, and Stephen S. Wise.
Judge and social reformer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Addams, Jane, -- 1860-1935 -- Correspondence; Annin, Joseph P. -- Correspondence; Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Baldwin, Roger N. -- 1884-1981 -- Correspondence; Beveridge, Albert Jeremiah, -- 1862-1927 -- Correspondence; Bok, Edward William, -- 1863-1930 -- Correspondence; Brandeis, Louis Dembitz, -- 1856-1941 -- Correspondence; Buchtel, Henry Augustus, -- 1847-1924 -- Correspondence; Burbank, Luther, -- 1849-1926 -- Correspondence; Catt, Carrie Chapman, -- 1859-1947 -- Correspondence; Causey, James H. -- Correspondence; Cavanaugh, John, -- 1870-1935 -- Correspondence; Costigan, Edward Prentiss, -- 1874-1939 -- Correspondence; Creel, George, -- 1876-1953 -- Correspondence; Darrow, Clarence, -- 1857-1938 -- Correspondence; Early, Stephen T. -- 1889-1951 -- Correspondence; Edison, Thomas A. -- 1847-1931 -- Correspondence; Ellis, Havelock, -- 1859-1939 -- Correspondence; Ely, Robert Erskine, -- 1861- -- Correspondence; Evans, Wainwright -- Correspondence; Ford, Harriet, -- 1868-1949 -- Correspondence; Ford, Henry, -- 1863-1947 -- Correspondence; Howe, Louis M. -- 1871-1936 -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Ickes, Harold L. -- 1874-1952 -- Correspondence; Johnson, Hiram, -- 1866-1945 -- Correspondence; Johnson, Tom Loftin, -- 1854-1911 -- Correspondence; Kellogg, John Harvey, -- 1852-1943 -- Correspondence; La Follette, Robert M. -- 1855-1925 -- Correspondence; Lasky, Jesse L., -- 1880-1958 -- Correspondence; Lippmann, Walter, -- 1889-1974 -- Correspondence; Mack, Julian W. -- 1866-1943 -- Correspondence; McAdoo, W. G. -- 1863-1941 -- Correspondence; McClure, S. S. -- 1857-1949 -- Correspondence; McDonald, Jesse F., -- 1858-1942 -- Correspondence; McIntyre, H. H. -- Correspondence; Miller, Justin, -- 1888-1973 -- Correspondence; Morgenthau, Henry, -- 1856-1946 -- Correspondence; O'Higgins, Harvey Jerrold, -- 1876-1929 -- Correspondence; Olson, Culbert Levy, -- 1876- -- Correspondence; Patterson, Thomas MacDonald, -- 1839-1916 -- Correspondence; Pearson, Drew, -- 1897-1969 -- Correspondence; Perkins, George W. -- 1862-1920 -- Correspondence; Pershing, James H. -- 1863-1948 -- Correspondence; Pinchot, Amos, -- 1873-1944 -- Correspondence; Pinchot, Gifford, -- 1865-1946 -- Correspondence; Richberg, Donald R. -- 1881-1960 -- Correspondence; Riis, Jacob A. -- 1849-1914 -- Correspondence; Roosevelt, Eleanor, -- 1884-1962 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Rosenblatt, Sol A., -- 1900- -- Correspondence; Russell, Bertrand, -- 1872-1970 -- Correspondence; Sanger, Margaret, -- 1879-1966 -- Correspondence; Schoff, Hannah Kent, -- 1853-1940 -- Correspondence; Shafroth, John F. -- 1854-1922 -- Correspondence; Shafroth, Morrison, -- 1888-1978 -- Correspondence; Sinclair, Upton, -- 1878-1968 -- Correspondence; Steffens, Lincoln, -- 1866-1936 -- Correspondence; Stowe, Lyman Beecher, -- 1880-1963 -- Correspondence